2022
DOI: 10.3390/diagnostics12040837
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning on Histopathological Images for Colorectal Cancer Diagnosis: A Systematic Review

Abstract: Colorectal cancer (CRC) is the second most common cancer in women and the third most common in men, with an increasing incidence. Pathology diagnosis complemented with prognostic and predictive biomarker information is the first step for personalized treatment. The increased diagnostic load in the pathology laboratory, combined with the reported intra- and inter-variability in the assessment of biomarkers, has prompted the quest for reliable machine-based methods to be incorporated into the routine practice. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 120 publications
0
28
0
Order By: Relevance
“…In another systematic review focused on CRC pathology image analysis using artificial intelligence found that while applications were still in early stages, the results were still promising with respect to accurately diagnosing CRC ( 16 ). Furthermore, in another systematic review focused on the use of deep learning for the diagnosis of CRC via histopathological images found that various studies have promise in aiding the diagnosis, predicting relevant molecular features, identifying prognostic features with correlations to metastasis, and assessing tumor microenvironments ( 17 ).…”
Section: Role Of Ai In Crc Diagnosticsmentioning
confidence: 99%
“…In another systematic review focused on CRC pathology image analysis using artificial intelligence found that while applications were still in early stages, the results were still promising with respect to accurately diagnosing CRC ( 16 ). Furthermore, in another systematic review focused on the use of deep learning for the diagnosis of CRC via histopathological images found that various studies have promise in aiding the diagnosis, predicting relevant molecular features, identifying prognostic features with correlations to metastasis, and assessing tumor microenvironments ( 17 ).…”
Section: Role Of Ai In Crc Diagnosticsmentioning
confidence: 99%
“…Since early detection of metastatic cancer has been absolutely emphasized for treatment and prognosis, innovative diagnostic methods are being studied [9][10][11][12][13][14], such as detecting cancerspecific markers through liquid biopsy besides the common diagnosis, including imaging examinations and histopathologic examinations. A liquid biopsy is a biological fluid sample that can be obtained from the body, such as blood, saliva, urine, or spinal fluid [15].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the works on CRC diagnosis direct their focus towards the classification of cropped regions of interest, or small tiles, instead of tackling the challenging task of diagnosing the entire WSI [18,19,17,20]. Notwithstanding, some authors already presented methods to assess the grading of the complete slide of colorectal samples.…”
Section: Introductionmentioning
confidence: 99%